2004
DOI: 10.1083/jcb.200405153
|View full text |Cite
|
Sign up to set email alerts
|

A role for BiP as an adjustor for the endoplasmic reticulum stress-sensing protein Ire1

Abstract: In the unfolded protein response, the type I transmembrane protein Ire1 transmits an endoplasmic reticulum (ER) stress signal to the cytoplasm. We previously reported that under nonstressed conditions, the ER chaperone BiP binds and represses Ire1. It is still unclear how this event contributes to the overall regulation of Ire1. The present Ire1 mutation study shows that the luminal domain possesses two subregions that seem indispensable for activity. The BiP-binding site was assigned not to these subregions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
314
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(325 citation statements)
references
References 40 publications
9
314
1
1
Order By: Relevance
“…Regions preceding and trailing it in the sequence are largely dispensable for regulation of Ire1, suggesting that cLD contains all necessary elements to sense unfolded proteins and transmit this information across the membrane. This result is in agreement with previous mutagenesis studies, which showed that segments can be deleted from either end of the LD without affecting its function (19,20). Second, the crystal structure of cLD defines two regions of extensive contacts at opposing ends of the monomeric cLD.…”
Section: Discussionsupporting
confidence: 82%
“…Regions preceding and trailing it in the sequence are largely dispensable for regulation of Ire1, suggesting that cLD contains all necessary elements to sense unfolded proteins and transmit this information across the membrane. This result is in agreement with previous mutagenesis studies, which showed that segments can be deleted from either end of the LD without affecting its function (19,20). Second, the crystal structure of cLD defines two regions of extensive contacts at opposing ends of the monomeric cLD.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, BiP interacts with both IRE1 and PERK and is a negative regulator of UPR activation (15,26). Although our structural studies did not identify a BiP interaction site, deletion studies in yeast and human IRE1, as well as in human PERK (17,18,27), suggest that a conserved BiP interaction site exists in the region C-terminal to residue Val-307 in human IRE1␣. It is interesting to note that the potential BiP interaction site in the crystal structure of human IRE1␣ is spatially conserved with that in the structure of yeast Ire1p (22).…”
Section: Discussionmentioning
confidence: 78%
“…However, the UPR represents a novel intracellular ER transmembrane signaling pathway, which appears to employ a ligand-independent activation mechanism (14) in which the IRE1 N-terminal luminal domain (NLD) functions as an ER stress sensor. According to this model, under normal conditions IRE1 is maintained in a monomeric state through interaction of the NLD with the ER resident chaperone BiP (15)(16)(17)(18)(19). Upon ER stress, immunoglobin-binding protein (BiP)͞glucose-regulated protein of 78 kDa (Grp78) (BiP) binds to unfolded proteins as they accumulate, permitting the released NLD to form homodimers.…”
mentioning
confidence: 99%
“…Few methods exist to assess global changes in misfolded protein accumulation. Biochemical techniques such as BiP/Kar2 sedimentation have been used to quantitate the chaperone binding to misfolded substrates [80]. However, until recently, no option was available for imaging intact cells.…”
Section: Approaches For Imaging Er Stress and Upr Activity In Livinmentioning
confidence: 99%